Conditioning and determining factors of the High Educational Inspection - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2022)
It investigates and goes deep into the main conditioning and determining factors that the High Inspection (AI) has had in these 40 years and more of existence, such as: its genesis as a product of the configuration of an autonomous State; the influence of the inspection power of the public powers through the different high inspections; its evolution, development and legal regulation; its hierarchical situation and dependency in the basic organic structures of the consequent Ministries of Education and finally, the sentences of the Constitutional Court that have delimited the competences that correspond to the State in this matter. The constitutional mandate is described in a decentralized political model of the inspection from the educational system and the positive contribution of the autonomic model in the global sphere of society and also in that of education. It is referred to the history and competencies of the high inspections of health, work and education that have opted for different organizational and action models. The work developed by the AI ​​and its different legal regulations that have marked four well-differentiated stages are explained. The main tasks of the IA have been listed and reflected in the annual reports of the State School Council in detail, where proposals for improvement appear, and also the main actions and the appeals presented for the non-compliance of basic regulations. The different ministerial organization charts are commented to reflect the functional direction that the AI ​​has had in the successive Ministries of Education that have existed. It concludes with some assessments and proposals to improve this institution.
Keywords: High Inspection; Education; Inspection; Autonomy; Competencies; State